The impact of artificial intelligence on the evaluation process - Teodora VASCAN (Acta et Commentationes, Sciences of Education, 2025)
The article is a study of how Artificial Intelligence can help us evaluate student products using the example of evaluating a report and an electronic presentation. Also in this article, a study was conducted on the trends of accessing various applications with Artificial Intelligence and chatbots in the Republic of Moldova, identifying which application dominates in searches. Also, evaluation sheets for reports and electronic presentations were created using Artificial Intelligence.